New generation genome sequencing methods - Kekeç, Ilgın; Sipahi, Nisa; İkiz, Serkan (Journal of Surgery and Medicine, 2022)
Sequencing procedures, which present information related to events in the living metabolism, are performed by genetic methods. Gene structure and genetic control mechanisms can be determined by sequencing methods, as they represent significant contributions to transcriptomic, ecological, and epidemiological studies. Thus, chromosomal abnormalities in living things with a whole genome analysis of different organisms (e.g., plants, bacteria, yeast, fungi, and viruses) are detected quickly, so that clinical disease can be diagnosed with reliable data from biomedical research. The nucleic acid sequencing processes have a history of about fifty years. With the technology developed in recent years, second and third-generation methods, known as next-generation sequencing (NGS), found their rightful place in the sector approximately 15 years ago. New-generation sequencing promotes inexpensive, routine, and comprehensive analyses of the living genome. In general, sequencing methods are separated as first-, second-, and third-generation sequencing methods, with the latter called ‘new-generation sequencing:’ our review focuses on these specific sequencing methods.